2001
DOI: 10.1053/jvet.2001.28435
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Ovariectomy Using Sequential Electrocoagulation and Sharp Transection of the Equine Mesovarium

Abstract: Standing laparoscopic ovariectomy, using electrosurgical instrumentation, is an effective and safe technique to provide hemostasis of the mesovarium in mares.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 20 publications
1
78
2
3
Order By: Relevance
“…A variety of methods have been reported for achieving hemostasis of the ovarian and uterine arteries during laparoscopic and non-laparoscopic ovariectomy and OHE in horses (Santschi et al 1995, Hooper et al 1992, Santschi and Slone 1995, Düsterdieck et al 2003, Rodgerson et al 2002, Ragle and Schneider 1995, Palmer 1993, Rodgerson et al 2001, Bouré et al 1997). In our study, hemostasis of the ovarian pedicle was consistently achieved by single application of a laparoscopic stapling instrument (60 mm / 3.5 mm staples).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of methods have been reported for achieving hemostasis of the ovarian and uterine arteries during laparoscopic and non-laparoscopic ovariectomy and OHE in horses (Santschi et al 1995, Hooper et al 1992, Santschi and Slone 1995, Düsterdieck et al 2003, Rodgerson et al 2002, Ragle and Schneider 1995, Palmer 1993, Rodgerson et al 2001, Bouré et al 1997). In our study, hemostasis of the ovarian pedicle was consistently achieved by single application of a laparoscopic stapling instrument (60 mm / 3.5 mm staples).…”
Section: Discussionmentioning
confidence: 99%
“…Subjective evaluation during surgery (Rodgerson et al 2001) and measurements in a previously cited pilot study (Düsterdieck et al 2003) indicated the ovarian artery was less than 3 mm in diameter.…”
Section: Blood Supply To the Urogenital Tractmentioning
confidence: 96%
See 1 more Smart Citation
“…Rodgerson et al 17 found that application of coagulation current from monoplar electrocautery alone was sufficient for effective hemostasis for equine mesoovarium. However, before final withdrawal of telescope in all the animals of laparoscopy groups the resected sites were closely observed.…”
Section: Intraoperative and Postoperative Observationsmentioning
confidence: 99%
“…Im hiesigen Patientengut kam es bei zwei von zehn Pferden zu schwerwiegenden Komplikationen mit Todesfolge, je einmal durch eine iatrogene Gefäß-verletzung sowie durch eine iatrogene Kolonverletzung. Somit bestätigten sich im untersuchten Patientengut die in der Literatur angeführten Risiken (Nickels 1988, Slone 1988 (Palmer 1993), der lineare Endostapler (Doran et al 1988, die bipolare HFChirurgie (Mariën et al 2000, Rodgerson et al 2001) sowie das Vessel-Sealing-System LigaSure ® einzeln oder in Kombination zum Einsatz (Hand et al 2002, Lloyd et al 2007). …”
Section: Sechsunddreißig Bis 48 Stunden Vor Dem Operativen Eingriff Eunclassified